How to deliver an effective primary survey report for the trauma CT: A radiological and surgical perspective. (April 2022) - Davies, Joseph; Johnson, Rowena; Kashef, Elika; Khan, Mansoor; Dick, Elizabeth
Whole body contrast-enhanced multidetector CT (WB-CE MDCT) is integral to the assessment of the severely injured patient with stable haemodynamic parameters or in those who respond to resuscitation with blood products. WB-CE MDCT is able to identify the number and severity of injuries sustained by the patient and enable time critical intervention. In this narrative review article we discuss how communication within the trauma team, including the radiologists and appropriate clinicians is crucial in optimizing the effectiveness of WB-CE MDCT. We review the time critical imaging findings and their clinical relevance, which should be included in a succinct CT primary survey report. We also discuss the process through which the effectiveness of the trauma report may be maximised and how non technical factors including teamwork may be optimised to facilitate decision making in this high pressure environment.